2005
DOI: 10.1152/ajpheart.00701.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection in chronically hypoxic rabbits persists on exposure to normoxia: role of NOS and KATP channels

Abstract: Hypoxia from birth increases resistance to myocardial ischemia in infant rabbits. We hypothesized that increased cardioprotection in hearts chronically hypoxic from birth persists following development in a normoxic environment and involves increased activation of nitric oxide synthase (NOS) and ATP-dependent K (K(ATP)) channels. Resistance to myocardial ischemia was determined in rabbits raised from birth to 10 days of age in a normoxic (Fi(O(2)) = 0.21) or hypoxic (Fi(O(2)) = 0.12) environment and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Different groups have reported iNOS upregulation during the exposition of rats to chronic hypoxia (62,114). Some reports indicate that eNOS is upregulated during rabbit (47) and rat (48) heart adaptation.…”
Section: Role Of No In the Regulation Of Heart Functionmentioning
confidence: 99%
“…Different groups have reported iNOS upregulation during the exposition of rats to chronic hypoxia (62,114). Some reports indicate that eNOS is upregulated during rabbit (47) and rat (48) heart adaptation.…”
Section: Role Of No In the Regulation Of Heart Functionmentioning
confidence: 99%
“…In the search of the mechanisms of ischemiareperfusion-induced pathways that may be amenable to manipulation, a number of potential candidates have been identified and have been the subject of many investigations. It is highly probable that a number of interaction mechanisms combine to determine the damage caused by ischemia-reperfusion in the myocardium, and a variety of such triggers have been postulated, including ionic disturbances and ion channels (30,69), fatty acid metabolism (35), ␣-and ␤-adrenergic receptors (67), various gene expression (53,60,64), platelet-activating factor (6), endothelin (50), nitric oxide (24), heme oxygenase-1 and carbon monoxide (5,61), and free radicals (15,30). It has been also shown that ischemia and reperfusion of the myocardium result in an activation of various pathways including caspase cascade, and it is hypothesized that a degree of caspase inhibition could be related to the recovery of postischemic cardiac function (4,31,57,62,66).…”
mentioning
confidence: 99%
“…Signaling mechanisms for implementing protective effect in chronic hypoxia have been hardly studied. We only know that they may include OR [6], protein kinase C [9], NO-synthase [4], mitoBKCa channels (mitochondrial large conductance Ca 2+ -dependent K + -channels) [2], KATP channels [4], and mitochondrial permeability transition (MPT) pore [14]. Analysis of the literature suggests that kinase that are tightly integrated with OR, for example, PI3 protein kinase, Akt, MEK1/2, ERK1/2, Src-protein kinase, and JAK2 may participate in the mechanism of protective action of CCNH [12].…”
Section: Resultsmentioning
confidence: 99%